História da educação rural em Pinhal da Serra (RS): práticas de mediação cultural (1963-1993) - Sgorla, Alana Silva (My University, 2020)
This study searchesthe everyday practices and analyses the representations about educational culture of rural schools in Pinhal da Serra (RS) city, from 1963 through 1993. The emancipation process of Pinhal da Serra takes place from 1996, so, this survey runs during the period when the territory was a district of Vacaria and, later, on Esmeralda. This research was made during the teachers magisterium. The survey is in the field of History of Education and has as theoretical reference the Cultural History. Its goal is to describe and assess representations about school culture of primary education institutions in Pinhal da Serra (RS) rural area, by collecting from the memory of two male and three female teachers, who taught in these schools during the period set by this period. For such purpose, it used Oral History (ALBERTI, 2004; FERREIRA, 2002; PORTELLI, 2016) and Documental Analysis (BACELLAR, 2005; LE GOFF, 1996; LUCHESE, 2014) as methodologies. Narrative analysis (CERTEAU, 2012; CHARTIER, 2002; HALBWACHS, 2006) of male and female teachers, based on Oral History, comprises memory as document. School and iconographic documents have been added to the empiry, provided by the interviewees and other located during the research process. The register of the local history of Campos de Cima da Serra, specifically of Pinhal da Serra, allowed to analysis of practices in the historical-cultural context on which they were developed. Sources indicate some characteristics of the course of history of education in the district studied, evidently showing the installation of Esmeralda (RS) determinated the organization of school institutions there are already on this project. And the amplification of the number of communities that were attended by schools. The teachers' narratives evidenciate the dimension of the rural teachers on rural the context research. It was possible to understand that the representations that exist in the memory of these people replace a time and space whey teachers put into practice the function of cultural mediators on the rural communities where these schools. The practice of cultural mediation done bay the rural teachers, in this area they happened on the specific context, directly related to the rural lifestyle and brought as traits the engagement in activities and they go beyond scholar space an invade social organization and cultural space of these rural communities.
Este estudo investiga as práticas cotidianas e analisa as representações sobre a cultura escolar das escolas rurais do município de Pinhal da Serra (RS), entre os anos de 1963 e 1993. O processo de emancipação de Pinhal da Serra ocorre a partir de 1996; assim, essa pesquisa transcorre no período em que o território foi distrito de Vacaria e, posteriormente, de Esmeralda. O recorte temporal dessa investigação compõe-se do período de magistério dos professores e professoras entrevistados. A pesquisa encontra-se no campo da História da Educação e tem, como referencial teórico, a História Cultural. Seu objetivo é descrever e analisar as representações sobre a cultura escolar das instituições de ensino primário do espaço rural de Pinhal da Serra (RS), através da memória de dois professores e três professoras que lecionaram nessas escolas no período estabelecido pelo recorte temporal. Para tal, utilizou-se como metodologia a História Oral (ALBERTI, 2004; FERREIRA, 2002; PORTELLI, 2016) e a Análise Documental (BACELLAR, 2005; LE GOFF, 1996; LUCHESE, 2014). A análise das narrativas (CERTEAU, 2012; CHARTIER, 2002; HALBWACHS, 2006) dos professores e professoras rurais, a partir da História Oral, compreende a memória como documento. Juntou-se à empiria documentos escolares escritos e documentos iconográficos, cedidos pelos entrevistados ou localizados durante o processo de pesquisa. O registro da história local dos Campos de Cima da Serra, especificamente de Pinhal da Serra, permitiu a análise das práticas no contexto histórico-cultural em que se desenvolveram. As fontes permitiram estabelecer algumas características no percurso da história da educação do município estudado, deixando evidente que a instalação de Esmeralda (RS) foi determinante para a organização das instituições escolares existentes e a ampliação do número de comunidades atendidas por escolas. As narrativas dos docentes evidenciam a dimensão da atuação dos professores e professoras rurais no contexto pesquisado. Foi possível compreender que as representações presentes nas memórias desses sujeitos, recompõem um tempo e um espaço onde os/as professores/as exerciam a função de mediadores culturais nas comunidades rurais onde estavam inseridas as escolas. As práticas de mediação cultural realizadas pelos/as professores/as rurais nesse território, aconteceram em um contexto específico, diretamente relacionado ao modo de vida rural e trouxeram como características o envolvimento em atividades em vão além do espaço escolar e invadem os espaços de organização social e cultural dessas comunidades rurais.
Keywords: Educação - História; Educação rural; Civilização - História; Education - History; Education, Rural; Civilization History